A Randomized Clinical Trial of a Palmtop Computer-Delivered Treatment for Smoking Relapse Prevention Among Women - Wetter, David W. (Psychol Addict Behav, 2011)
Relapse is the rule rather than the exception among smokers attempting to quit, and compared to men, women may have higher relapse rates. The current study was a randomized clinical trial testing a palmtop computer-delivered treatment for smoking relapse prevention among women. The intervention was individualized based on key theoretical constructs that were measured using ecological momentary assessment (EMA). All participants (N=302) received standard smoking cessation treatment consisting of nicotine replacement therapy and group counseling, and completed EMA procedures for one week after quitting. At the completion of the group counseling sessions and EMA procedures, participants were randomized to either computer-delivered treatment (CDT) or no further computer-delivered treatment or assessment (EMA-Only). CDT participants received a palmtop computer-delivered relapse prevention treatment for one additional month. CDT did not improve abstinence rates relative to EMA-Only. Process analyses suggested that heavier smokers were more likely to use CDT and that greater use among CDT participants may be associated with more positive outcomes. The rapid pace of technological advances in mobile computer technology and the ubiquity of such devices provide a novel platform for developing new and potentially innovative treatments. However, the current study did not demonstrate the efficacy of such technology in improving treatment outcomes.